1691. Bacteriophage and Protein Synthesis Pathway Inhibitor Combinations: Antibiotic mechanism of action drives antagonistic interactions. (15th December 2022) - Kunz Coyne, Ashlan J; Bhutani, Natasha; Holger, Dana; Kebriaei, Razieh; Stamper, Kyle; Ghali, Amer El; Ghali, Amer El; Alexander, Jose; Biswas, Biswajit; Lehman, Susan; Arias, Cesar A; Rybak, Michael J
Abstract: Background: Bacteriophage (phage) to augment antibiotic efficacy is a possible therapeutic option in the era of antimicrobial resistance. Studies to date have assessed phage-antibiotic synergy (PAS), however, its efficacy may be dependent upon antibiotic mechanism of action. Here, we report our in-vitro evaluation of phage-antibiotic antagonism (PAA) among phage and protein synthesis inhibitor combinations in multidrug-resistant clinical strains of P. aeruginosa, S. aureus, and E. faecium . Methods: The following bacteria (phage) regimens were evaluated: 10266 (EM) and R9010 (14207) ( P. aeruginosa ) against gentamicin (GEN), azithromycin (AZM), and ciprofloxacin (CIP); N315 and 494 (Intesti) ( S. aureus ), and R497 and HOU503 (NV-497) ( E. faecium ) against linezolid (LNZ), minocycline (MIN), and daptomycin (DAP). Modified checkerboard (CB) MIC assays were used for preliminary screening followed by 24h time kill analyses (TKA). For CB, synergy, additive activity, and antagonism were defined as an FIC index of ≤0.5, 1–4, and >4, respectively. In 24h TKA, synergy and additivity were defined as a ≥2 and ≥1 log10 CFU/mL reduction from baseline, while antagonism was defined as phage-antibiotic combinations with CFU/mL higher than the most effective single treatment at 24h. Data were compared by one-way ANOVA and Tukey (HSD) test (P< 0.05). Results: In CB analyses and 24h TKA of S. aureus and E. faecium isolates, phage-LZD and phage-MIN combinations were antagonistic (FIC >4) while phage-DAP was synergistic (FIC 0.5) (ANOVA range of mean differences 0.52 to 2.59 log10 CFU/mL; P< 0.001). For P. aeruginosa, phage-AZM and phage-GEN were antagonistic (FIC >4) and additive (FIC=1), respectively (ANOVA range of mean differences 1.04 to 1.95 log10 CFU/mL; P< 0.001). Conclusion: Our results suggest that antibiotics that act on the protein synthesis pathway may lead to PAA, however, PAA interactions may be highly dependent upon antibiotic mechanism of bacterial inhibition (i.e., location of ribosomal protein synthesis inhibition, bactericidal vs. bacteriostatic) protein synthesis inhibit. Studies assessing PAA in a wider array of phage-antibiotic combinations are warranted. Disclosures: Cesar A. Arias, MD, PhD, Entasis Phramceuticals: Grant/Research Support|MeMed Diagnostics: Grant/Research Support|Merck: Grant/Research Support.